Rebel Girls and Consequence in Life Is Strange and The Walking Dead. Issue 4 (June 2019) - Butt, Mahli-Ann Rakkomkaew; Dunne, Daniel
The presence of women within videogames has progressed to a state where narratives about the empowerment of women are becoming popular; however, such games still invite a number of gendered stereotypes. Housed in the genre of adventure games, The Walking Dead: Season Two and Life Is Strange appear to follow in the spirit of this emerging women's revolution but inevitably reestablish traditional presentations of sexism in the treatment of their endings. In particular, the presentation of the infamous Trolley Problem and its inherent utilitarian framework is an incendiary moment wherein these games mark rebellious women as necessary sacrifices for the greater good and the continuation of the community. This article explores these two specific moments of sacrifice at the conclusions of Life Is Strange and The Walking Dead: Season Two and engages with tensions between the status quo and the resistances that challenges these norms.